SERÖZ OVER TÜMÖRLERİNDE GHRELİN VE OBESTATİN EKSPRESYONU - NURKALEM, CEMİLE (Fırat Üniveristesi, 2009)
Over tümörleri, jinekolojik maligniteler arasında en ölümcül seyredendir. Over kanserlerinin kesin etyolojisi halen bilinmektedir. Seröz over tümörleri en sık görülen epitelial over malignitesidir.Benign, bordeline ve malign seröz tümörlü gruplarda ghrelin ve obestatinin hastalığın fizyopatojisi ve prognozunda olası etkilerinin olup olmadığı araştırılması planlanmıştır. Benign, borderline ve malign gruplarına ayrılan toplam 47 seröz over tümörlü olgu, retrospektif olarak immunohistokimyasal metodlar ile ghrelin ve obestatin ekspresyonu araştırılmıştır.Seröz over tümörlerinin benign, borderline ve malign gruplarında hem ghrelin hem obestatin ekspresyonu izlendi. Benign grupta ghrelin ekspresyonu anlamlı olarak yüksekti, obestatin ekspresyonuda gruplar arasında anlamlı farklılık izlenmedi. Gruplar demografik özellikler, risk faktörleri, cerrahi evre, tümör markerleri ve sağ kalım süreleri açısından karşılaştırıldı. Tüm grupların yaş ortalaması 47.78 15.34 idi. Malign grupta yaş ortalamasında anlamlı fark vardı (p<0,05). CA-125 malign grupta anlamlı olarak yüksek izlendi (p<0,05). Malign grupta menapoz oranında anlamlı fark vardı (p<0,05).Sonuç olarak ghrelinin seröz over tümörlerinin gelişiminde anti-prolifertaif etkilerinin olabileceğini düşündürmektedir.Overdeki neoplastik transformasyonda, ghrelin ve obestatinin potansiyel etkilerinin belirlenmesi için daha ileri çalışmalara ihtiyaç vardır.Anahtar Kelimeler: Seröz over tümörleri, ghrelin, obestatin

Ovarian tumours are the most lethal cancer among gynecologic malignancies. The exact etiology of ovarian tumors remains still unsolved. Serous ovarian tumours are the most common in epithelial ovarian tumours.This study was planned to research whether ghrelin and obestatin are expressed in benign, bordeline and malign serous ovarian tumours, their possible role in ovarian tumours physiopathology and prognoses.In this study we investigated immunohistochemistry methods of ghrelin and obestatin in 47 cases diagnosed as serous ovarian tumours by retrospective.In the benign, borderline and malign ovarian tumors it was shown that ghrelin and obestatin was expressed together. The expression in benign group was much higher in the comparision with other groups. A meaningful variance has been detected in the tissue of these three groups in ghrelin expression. A meaningful variance has not been detected in the tissue of these three groups in obestatin expression. Demographic characteristics, risc factors, surgical stage, tumour marcers and overall survival were evaluated these three groups. Mean age of all groups are 47.78 15.34. There was a meaningful difference in median age at malign group (p<0,05). There was a meaningful difference in ratio of menapouse at malign group (p<0,05). CA-125 levels higher at malign group (p<0,05).In conclusion, our results demostrate that effect of ghrelin in serous ovarian carcinoma can have anti-proliferatif activity.Neoplastic transformation of the ovary, the potentiel actions of ghrelin and obestatin merit further investigation.Key Words: Serous ovarian tumours, ghrelin, obestatin
The expression of ghrelin and obestatin in serous ovarian tumours
Keywords: Kadın Hastalıkları ve Doğum